1987
DOI: 10.1530/jrf.0.0810525
|View full text |Cite
|
Sign up to set email alerts
|

Uterine blood flow during the development and regression of the decidual cell reaction in ovariectomized, steroid-treated mice

Abstract: Summary. Uterine blood flow was assessed in mice by measuring organ uptake of intravenously injected [14C]butanol. In ovariectomized mice, injection of 100 ng oestradiol\x=req-\ 17\g=b\ increased blood flow 5-fold over that of untreated controls. The injection of oestradiol-17\g=b\ in progesterone-treated mice also increased uterine blood flow at the time of maximal sensitivity to a decidual stimulus, but not 4 days later. Absolute values of blood flow increased during development of the decidual cell reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…4), despite the use of a different technique for the BF assessment. In addition, the absence of a change in relative uterine BF during early decidualization for the rat is consistent with findings for the mouse [26], where increases in uterine BF also matched the increases in uterine weight. It is doubtful that increases in absolute BF contribute to the extravasation of tracer proteins since significant uterine weight gains and the concomitant BF increases are not observed until after the accumulation of tracer proteins is observed.…”
Section: Discussionsupporting
confidence: 84%
“…4), despite the use of a different technique for the BF assessment. In addition, the absence of a change in relative uterine BF during early decidualization for the rat is consistent with findings for the mouse [26], where increases in uterine BF also matched the increases in uterine weight. It is doubtful that increases in absolute BF contribute to the extravasation of tracer proteins since significant uterine weight gains and the concomitant BF increases are not observed until after the accumulation of tracer proteins is observed.…”
Section: Discussionsupporting
confidence: 84%
“…It is well established that an increase in endometrial vascular permeability precedes implantation and decidualization, and appears to be a prerequisite for these events (Psychoyos, 1973;Kennedy, 1986). In addition, enlargement of uterine blood vessels and extensive neovascularization of the uterus occur after application of stimuli that induce decidualization (Lobel et al, 1965), as does a rapid increase in uterine blood flow (Edwards & Milligan, 1987). Prostaglandins (PGs), particularly those of the E series, have been implicated as key mediators of the increased endometrial vascular permeability and subsequent decidualization; it has also been suggested that the production of other vasoactive mediators, in addition to PGs, by the endometrium may be essential for some of these reactions to occur (Kennedy, 1980a).…”
Section: Introductionmentioning
confidence: 99%
“…An antibody administered by ip injection is taken into the blood stream through the peritoneum and diaphragm [42,43], and its blood concentration is as high as that with intravenous injection after 15 h [42]. As blood flow in the uterus is raised by progesterone and estrogen during the implantation period [44], it was assumed that antibodies were smoothly delivered to the uterine tissue. Inhibitors of LIF applied by the intraluminal route did not completely disrupt implantation in most strains of mice, apart from C57BL/6J [29][30][31]; this is partly because the potential of LIF to promote implantation in the stroma in these strains is not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…flow in the uterus is raised by progesterone and estrogen during the implantation period [44], it was assumed that antibodies were smoothly delivered to the uterine tissue. Inhibitors of LIF applied by the intraluminal route did not completely disrupt implantation in most strains of mice, apart from C57BL/6J [29][30][31]; this is partly because the potential of LIF to promote implantation in the stroma in these strains is not negligible.…”
Section: Anti-lif Antibody On Implantation 705mentioning
confidence: 99%